1992
DOI: 10.3109/02713689209000742
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β modulates effects of epidermal growth factor on corneal epithelial cells

Abstract: In order to understand the mechanisms that bring about maintenance and restoration of the integrity of corneal epithelium, we investigated independent and combined effects of transforming growth factor-beta (TGF-beta) and epidermal growth factor (EGF) on rabbit corneal epithelial cells in cell and organ culture. Specifically, we determined whether incubation with these factors influenced 1) cellular proliferation, 2) ability of cells to attach to a fibronectin matrix, and 3) the rate of epithelial migration ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 24 publications
0
24
1
2
Order By: Relevance
“…TGF-p, causes a dose-related inhibition of epi thelial cell proliferation by inhibiting the stimulatory effects of EGF [3,4], In our clinical series there is a tendency for relatively late epithelial healing in patients with higher abla tion depth [personal commun.]. The results of our study showed that aqueous TGF-(3, levels increase after deeper ablation; the dose-related inhibition of EGF by TGF-(3, may be the reason of the delayed epithelial healing in high myopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-p, causes a dose-related inhibition of epi thelial cell proliferation by inhibiting the stimulatory effects of EGF [3,4], In our clinical series there is a tendency for relatively late epithelial healing in patients with higher abla tion depth [personal commun.]. The results of our study showed that aqueous TGF-(3, levels increase after deeper ablation; the dose-related inhibition of EGF by TGF-(3, may be the reason of the delayed epithelial healing in high myopes.…”
Section: Discussionmentioning
confidence: 99%
“…16-0380 $12.00/0 E-Mail kargerer/ kargcr.ch Fax +4161 30612 34 http://www.karger.ch [2], In addition TGF-P suppresses matrix degradation by collagénases, it decreases the synthesis o f proteases that de grade matrix metalloproteinases and increases the synthesis of protease inhibitors that block the activity of such proteas es [1,3]. TGF-P, causes dose-related inhibition of epithelial cell proliferation by inhibiting the stimulatory effects of epidemial growth factor (EGF) [4], TGF-Pi and TGF-pn have been found in aqueous humor and have been postulat ed to mediate the immunosuppressive properties of this fluid [5,6]. deepithelialization; group 3 = mechanical corneal deepithelialization followed by 50-um excimcr laser photoablation; group 4 = mechanical corneal deepithelialization followed by 100-um excimer laser photoablation.…”
Section: Introductionmentioning
confidence: 99%
“…MISHIMA et al [230] demonstrated that TGF-b could antagonise EGF-induced attachment of cells onto a fibronectin matrix, migration over corneal stroma, and proliferation of corneal epithelial cells. TGF-b was also found to inhibit the EGF-induced filapodia extension associated with migrating human bronchial epithelial cells [231].…”
Section: Functions Of Egfr Ligandsmentioning
confidence: 99%
“…Pres ence of their corresponding mRNA and/or of the growth factor itself and/or its receptors has been reported by numerous authors using various approaches. Epidermal growth factor (EGF), EGF receptor, fibroblast growth factor (FGF), transforming growth factor b (TGFb) mRNA have been detected in corneal epithe lial cells [1]; EGF and FGF were immunolocalized in these cells [2,3] together with their receptors [4] as well as PDGF [5], They could be stimulated to proliferate with exogenous addition of EGF, FGF-a and FGF-b, PDGF, TGFb [6][7][8], Interestingly, these four latter growth factors have the ability to bind to hep-arin and are believed in vivo to be associated with the extracellular matrix (ECM) via inter actions with proteoheparan sulfates as demon strated for FGFs in the Bowman membrane [9], By this association growth factors are pro tected against proteolysis and ECM could be described as a storage compartment for growth factors. From these storage sites, they could be released and become bioavailable to stimulate cell migration, proliferation and dif ferentiation in order to replace dying or dam aged cells.…”
mentioning
confidence: 99%